THE USE OF THE ONLINE CALCULATOR «GEOGEBRA» IN MATHEMATICS LESSONS (Innovative professional education, 2025)
The article emphasizes the importance of integrating digital technologies into the educational process and demonstrates how GeoGebra can contribute to a deeper understanding of mathematics among students in vocational education institutions. Practical examples of using GeoGebra for solving equations, analyzing geometric figures, and conducting statistical research are provided.
Keywords: GeoGebra, online calculator, visualization, mathematics, vocational education, analytical thinking, dynamic modeling, graphs, mathematical calculations